A localization method for subsea pipeline based on active magnetization. (1st February 2023) - Huang, Xinjing; Wang, Yuan; Ma, Jinyu; Wu, Jialin; Li, Jian; Zhang, Yu; Feng, Hao
Abstract: Accurate location of subsea pipelines is a prerequisite for real-time tracking and detailed inspections by underwater robots. The magnetic anomalies generated by ferromagnetic pipelines can be used to locate both exposed and buried pipelines. However, due to the low signal ratio and model inconsistencies under weak and variable ambient magnetization, there is currently no intuitive and reliable pipeline detection method for pipeline tracking. This paper proposes a method capable of immediately and accurately locating pipelines via active magnetization and vertical magnetic measurements. Finite element simulations show that a magnet array can significantly enhance the magnetic anomaly, and that the vertical magnetic component alone can accurately indicate the pipeline's position, avoiding the inconvenience of magnetic three-component alignment in the field. It is experimentally demonstrated that the magnetic detection signal-to-noise ratio can be significantly increased by 5 dB–20 dB for a Φ219 mm steel pipe using the magnet array, and the maximum lateral positioning error is 0.03 m and much smaller than that without the magnet array.